Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
[tex]f'(\dfrac{\sqrt3}{2})[/tex] = 2
Explanation:
Given that,
[tex]f(x)=\sin^{-1} x[/tex]
We need to find the value of [tex]f'(\dfrac{\sqrt3}{2})[/tex]
First, we take f'(x). We know that,
[tex]\dfrac{d}{dx}(\sin^{-1} x)=\dfrac{1}{\sqrt{1-x^2} }\\\\f'(x)=\dfrac{1}{\sqrt{1-x^2} }\\\\f'(\dfrac{\sqrt3}{2})=\dfrac{1}{\sqrt{1-(\dfrac{\sqrt3}{2})^2} }\\\\=\dfrac{1}{\sqrt{1-(\dfrac{3}{4})} }\\\\=\dfrac{1}{\sqrt{\dfrac{1}{4}}}\\\\=\dfrac{1}{\dfrac{1}{2}}\\\\=2[/tex]
So, the value of [tex]f'(\dfrac{\sqrt3}{2})[/tex] is 2.
The value of "[tex]f'(\sqrt{\frac{3}{2} } )[/tex]" will be "2".
Given that:
- [tex]f(x) = sin^{-1} x[/tex]
We know that,
→ [tex]\frac{d}{dx} (sin^{-1} x) = \frac{1}{\sqrt{1-x^2} }[/tex]
Now,
→ [tex]f'(x) = \frac{1}{\sqrt{1-x^2} }[/tex]
then,
→ [tex]f'(\frac{\sqrt{3} }{2} ) = \frac{1}{1-(\frac{\sqrt{3} }{2} )^2}[/tex]
By opening the square, we get
[tex]= \frac{1}{\sqrt{1-(\frac{2}{4} )} }[/tex]
[tex]= \frac{1}{\sqrt{\frac{1}{4} } }[/tex]
[tex]= \frac{1}{\frac{1}{2} }[/tex]
[tex]= 1\times \frac{2}{1}[/tex]
[tex]= 2[/tex]
Thus the above answer is right.
Learn more about function f(x) here:
https://brainly.com/question/17032105
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.